2018
DOI: 10.1136/bmjopen-2017-018208
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the characteristics of recurrent visits to the emergency department by paediatric patients: a retrospective observational study conducted at three tertiary hospitals in Korea

Abstract: ObjectivesThe number of paediatric patients visiting the emergency department (ED) continues to rise. In South Korea, approximately 25% of the patients who visit the ED are paediatric patients. In the USA, about 20% of the paediatric population were found to have visited the ED in the past year. A recent study demonstrated that 4.5%–8% of patients account for 25% of all ED visits. Therefore, the aim of this study was to identify the characteristics of recurrent visits.MethodsDesign: retrospective observational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…This proportion is considerably higher than in previous reports of 30-40% of non-urgent visits in pediatric emergency care centers in Canada and Australia [19,34], 40% in Belgium and Italy [35,36] and 60% in the United States [37] . However, the tendency to provide primary care by tertiary health care institutions is described as global problem and one reason for growing health expenses [20]. In a study from the UK, no association between non-urgent presentations and the asylum-status was found [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This proportion is considerably higher than in previous reports of 30-40% of non-urgent visits in pediatric emergency care centers in Canada and Australia [19,34], 40% in Belgium and Italy [35,36] and 60% in the United States [37] . However, the tendency to provide primary care by tertiary health care institutions is described as global problem and one reason for growing health expenses [20]. In a study from the UK, no association between non-urgent presentations and the asylum-status was found [38].…”
Section: Discussionmentioning
confidence: 99%
“…It may also result in increased numbers of presentations with non-urgent conditions at emergency departments. There is a global trend of an increase in non-urgent visits at emergency departments in high-income countries, which could also potentially be prevented by primary health care [18][19][20][21]. Asylum-seeking children are at risk of lacking integration into the primary health care system and may therefore have higher rates of ambulatory-care-sensitive admissions and non-urgent emergency-department presentations than their local peers.…”
Section: Introductionmentioning
confidence: 99%
“…A similar age distribution in pediatric emergency department visits was seen in other parts of the world. A Californian and a Korean study both showed frequent visits to emergency departments were more common in children aged 1 to 4 years [31,32]. However, these studies did not detail if asylum-seeking children were included.…”
Section: Discussionmentioning
confidence: 99%
“…A similar age distribution in paediatric emergency department visits was seen in other parts of the world. A Californian and a Korean study both showed frequent visits to emergency departments were more common in children aged 1 to 4 years (29,30). However, these studies did not detail if asylum-seeking children were included.…”
Section: Discussionmentioning
confidence: 99%